The Effect of Academic Services on Student Satisfaction Faculty of Social Sciences and Law, Manado State University - Margareth Rantung; Nancy Melisa Onibala; Chintya Maria Siwi; Jeane Mantiri (Jurnal Manajemen Pelayanan Publik, 2024)
Satisfaction refers to the level of feelings after comparing the perceived performance or results within expectations.Higher education leads to a place or forum to produce qualified human resources. The purpose of this study was to determine the extent of the influence of Student Satisfaction on Academic Services at the Faculty of Social and Law Sciences, State University of Manado to improve quality-based service quality. This research was conducted in the even semester, namely in the academic year 2021/2022. The technique of collecting data is using a questionnaire. There has been no research conducted on the effect of academic services on student satisfaction at the Faculty of Social and Law Sciences, State University of Manado, so this research is expected to improve the quality of academic services. Based on the analysis results obtained Ŷ = 3.105 +1.114 x where academic services have a verifiable effect on student satisfaction at the Faculty of Social Sciences and Law, State University of Manado.The results of the correlation show that the value of r = 0.874 proves that the relationship between Academic Services (Variable X) and Student Satisfaction (Variable Y) has a close relationship.